Impact of Ferrous Iron on Microbial Community of the Biofilm in Microbial Fuel Cells - Liu, Qian; Liu, Bingfeng; Li, Wei; Zhao, Xin; Zuo, Wenjing; Xing, Defeng (Frontiers in Microbiology, 2017)
The performance of microbial electrochemical cells (MECs) depends upon microbial community structure and metabolic activity of the electrode biofilms. Iron as a signal affects biofilm development and enrichment of exoelectrogenic bacteria. In this study, the effect of ferrous iron on microbial communities of the electrode biofilms in microbial fuel cells (MFCs) was investigated. Voltage production showed that ferrous iron of 100 μM facilitated MFC start-up compared to 150 μM, 200 μM and without supplement of ferrous iron. However, higher concentration of ferrous ion had an inhibitive influence on current generation after 30 days of operation. Illumina Hiseq sequencing of 16S rRNA gene amplicons indicated that ferrous iron changed obviously microbial community structures of both anode and cathode biofilms. Principle component analysis (PCA) showed that the response of microbial communities of the anode biofilms to higher concentration of ferrous iron was more sensitive. The majority of predominant populations of the anode biofilms in MFCs belonged to Geobacter, which was different from the populations of the cathode biofilms. An obvious shift of community structures of the cathode biofilms occurred after ferrous iron addition. This study implied that ferrous iron influenced the power output and microbial community of microbial fuel cells.